Fertility and Modernity. Issue 642 (2nd November 2021) - Spolaore, Enrico; Wacziarg, Romain
Abstract: We investigate the determinants of the fertility decline in Europe from 1830 to 1970 using a newly constructed data set of linguistic distances between European regions. The decline resulted from the gradual diffusion of new fertility behaviour from French-speaking regions to the rest of Europe. Societies with higher education, lower infant mortality, higher urbanisation and higher population density had lower levels of fertility during the nineteenth and early twentieth centuries. However, the fertility decline took place earlier in communities that were culturally closer to the French, while the fertility transition spread only later to societies that were more distant from the frontier. This is consistent with a process of social influence, whereby societies that were culturally closer to the French faced lower barriers to learning new information and adopting novel attitudes regarding fertility control.